1988
DOI: 10.1016/0014-5793(88)80141-8
|View full text |Cite
|
Sign up to set email alerts
|

Acidic fibroblast growth factor stimulates opsin levels in retinal photoreceptor cells in vitro

Abstract: It is demonstrated that newborn rat retinal photoreceptor cells can differentiate in monolayer culture, and synthesize de novo photoreceptor-specific proteins such as opsin. When maintained in serum supplemented medium on a laminin substrate, these cells survive for up to 3 weeks. The addition of acidic fibroblast growth factor stimulates an increase in the levels of opsin of 5-IO-fold control values, and prolongs cell survival by up to 6 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 13 publications
0
18
1
Order By: Relevance
“…A number of factors, in addition to RA, have been shown to promote rod photoreceptor cell differentiation in retinal cell cultures, including cilliary neurotrophic factor (18), acidic fibroblast growth factor (19), basic FGF (20), and taurine (21). It could be that expression of several of these factors is enhanced by RA in the retina as RA is known to induce the expression of several growth factors in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors, in addition to RA, have been shown to promote rod photoreceptor cell differentiation in retinal cell cultures, including cilliary neurotrophic factor (18), acidic fibroblast growth factor (19), basic FGF (20), and taurine (21). It could be that expression of several of these factors is enhanced by RA in the retina as RA is known to induce the expression of several growth factors in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…As exogenous FGF are known to increase survival of neuronal cells such as photoreceptors (11,17,18), cholinergic neurons, and retinal ganglion cells (51), in view of our data, the survival activity of exogenous FGF should depend on an increase in the expression of FGF1 or FGF2 in these neuronal cells.…”
Section: Fig 9 Activation Of Erk1 By Fgf1 Fgfmentioning
confidence: 99%
“…These patterns of FGF expression suggest that these growth factors are involved in the integrity, development, and differentiation of the central nervous system. In fact, in vitro studies have shown that FGF1 promotes the survival of photoreceptors (11) and the neuritic outgrowth of dissociated retinal ganglion cells (12). FGF1 also inhibits pigmentation of immature pigmented epithelium cells of embryonic chick retina and stimulates ganglion cell differentiation (13).…”
Section: Fgf1mentioning
confidence: 99%
“…Surprisingly, BDNF reduced the incidence of macrophages from that seen in light-damaged retinas (Figs. 2C and 3C (17,20,21); aFGF (35) and bFGF (16) prolong photoreceptor survival in vitro; and BDNF (2, 7) and CNTF (36) Light damage is thought to result from the generation of oxygen free radicals and the ensuing peroxidation of lipids (37), and when viewed in the microscope, outer segments usually are the first part of the photoreceptor cell to exhibit damage (38,39). Preservation, by the injected factors, of some intact outer segments in most of the rescued retinas indicates that these agents actually protect the cells from damage at an early stage in the injury event.…”
Section: Quantification Of Photoreceptor Rescue and Macrophagementioning
confidence: 99%